Simulated energetic particle transport in the interplanetary space: The Palmer consensus revisited. Issue 2 (26th February 2013) - Tautz, R. C.; Shalchi, A.
Abstract : [1] Reproducing measurements of the scattering mean free paths for energetic particles propagating through the solar system has been a major problem in space physics. The pioneering work of Bieber et al. (1994) provided a theoretical explanation of such observations, which, however, was based on assumptions such as the questionable hypothesis that quasi‐linear theory is correct for parallel diffusion. By employing a hybrid plasma‐wave/magnetostatic turbulence model, a test‐particle code is used to investigate the scattering of energetic particles. The results show excellent agreement with solar wind observations. Key Points: Cosmic‐ray mean‐free paths are reproduced with test‐particle simulations A new hybrid plasma wave/magnetostatic models the Solar wind turbulence The results show excellent agreement with Palmer consensus range observations